A Smart Real Time Ridesharing And Travel Assistance (International Journal of Engineering and Computer Science, 2015)
: India is the second populous country in the world. India’s population is about 1.1 billion with an overall density of 336 people persquare kilometer. Indian public transport supports various mode of transport such as transport by land, water, air. More than 30% of Indianpopulation is car owners. Traffic is mainly high during peak hours within the cities [2]. In order to reduce traffic congestion, a real timeridesharing is proposed. This method is implemented by developing an android application which is user friendly and has high mobility.Real-time ridesharing is an extension of carpooling to best suite one's preferences using the data collected from social networking. It enablesusers especially colleagues, classmates, to share their vehicles for travelling to the same destination or nearby destination. In addition to ridesharing,the system gives real time navigation guidance in a map. Users can set their travel to be private or make it available to some of theirfriends using privacy settings. The concept facilitates to include taxis or rickshaws and also other public transport systems which can settheir visibility to public. In case of public transport, passengers can request to board a particular vehicle by looking up the available servicesin the admin processes and the requests from various users, notifies to them the nearest stopping. Implementation requires integration fromsocial networking sites, location identified using GPS, intelligent processing of the data collected and history maintenance. For ease of usethis is incorporated in mobile phones which make use of collection of social networking information and GPS data. This system supports theuse of mass public transport system and travelling together which in future may become mandatory to control the depletion of fuel, make theenvironment green and to control traffic.